Database security - Basta, Alfred; Bullaboy, Dana; Zgola, Melissa (Course Technology/Cengage Learning, 2012)
As a society that relies on technology to thrive, we face a growing number of potentially catastrophic threats to network security daily. This title delivers the know-how and skills that professionals must have to protect their company's technology infrastructures, intellectual property, and future prosperity